2000
DOI: 10.1136/gut.47.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil antibodies associated with ulcerative colitis interact with the antigen(s) during the process of apoptosis

Abstract: Background-Cell death by apoptosis seems to be an important mechanism for translocation to the cell surface of a variety of intracellular components capable of inducing autoantibody production. Aims-To identify the cellular location of antigen (Ag)-antineutrophil cytoplasmic antibodies (ANCA) in non-apoptotic human neutrophils, and to assess if ANCA associated with ulcerative colitis reacts with neutrophil antigen(s) during neutrophil apoptosis. The cellular distribution of Ag-ANCA in apoptotic neutrophils was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Th ese results are in agreement with other recent investigations, which strongly suggest that diff erent autoantigens are responsible for the pANCA immune response in patients with IBD. Th ese autoantigens are thought to be located not only in the cytoplasm of the granulocyte but also inside the granulocyte nucleus (histone 1, nonhistone chromosomal protein, high mobility group) [17,[27][28][29][30][31], with exhibited sensitivity on DNA-se treatment [17,27]. In agreement with the fi ndings of some other investigators [32][33][34], we found a positive reaction with cathepsin-G in two cases of UC; however, this specifi city was not signifi cantly diff erent from the control group, where two samples also tested positive with cathepsin-G.…”
Section: Discussionmentioning
confidence: 99%
“…Th ese results are in agreement with other recent investigations, which strongly suggest that diff erent autoantigens are responsible for the pANCA immune response in patients with IBD. Th ese autoantigens are thought to be located not only in the cytoplasm of the granulocyte but also inside the granulocyte nucleus (histone 1, nonhistone chromosomal protein, high mobility group) [17,[27][28][29][30][31], with exhibited sensitivity on DNA-se treatment [17,27]. In agreement with the fi ndings of some other investigators [32][33][34], we found a positive reaction with cathepsin-G in two cases of UC; however, this specifi city was not signifi cantly diff erent from the control group, where two samples also tested positive with cathepsin-G.…”
Section: Discussionmentioning
confidence: 99%
“…33 Synchronization was confirmed by staining fibroblasts with propridium iodide/ RNase staining buffer (BD) 24 hours or 72 hours after serum addition or drug removal, which was examined by confocal microscopy. 34 To measure mitochondria distribution in synchronized fibroblasts, fibroblasts were plated on chamber slides after serum starvation or drug treatment for 24 hours in regular minimum essential medium supplemented with 10% fetal bovine serum and then transfected with mito-DsRed2. 48 hours after transfection, cells were fixed, immunostained, and examined as described below.…”
Section: Flow Cytometric Analysis and Fibroblast Synchronizationmentioning
confidence: 99%
“…For IgG class ANCA, several proteins of the cytosol (actin, catalase, enolase) and the azurophilic (bactericidal/permeability increasing protein, cathepsin G) or specific granules (lactoferrin) have been suggested as target antigens [29,32]. Recent studies described nuclear proteins, particularly of the nuclear periphery, as candidate proteins of ‘atypical’ p‐ANCA [33–36]. Using enzyme‐linked immunosorbent assays, we could not demonstrate any reactivity of IgA class ANCA with the aforementioned cytosolic and granular proteins (data not shown).…”
Section: Discussionmentioning
confidence: 84%